Ensuring the Future: A Comprehensive Review of Digital Preservation Strategies - Singh, Kapila (Journal of Advanced Research in Library and Information Science; Vol 11 No 1 (2024): Journal of Advanced Research in Library and Information Science, 2024)
In the digital age, preserving our cultural heritage, scholarly knowledge, and institutional records has become paramount. However, the ephemeral nature of digital information presents significant challenges to long-term preservation. This review article examines various strategies, technologies, and best practices in digital preservation. From the fundamentals of data integrity to advanced emulation techniques, this comprehensive overview aims to provide insights into the evolving landscape of digital preservation and its critical importance in safeguarding our collective memory. By delving into topics such as migration, emulation, metadata management, and the Open Archival Information System (OAIS) reference model, this review sheds light on the multifaceted nature of digital preservation and offers guidance for practitioners and researchers alike. Through a synthesis of current research and industry practices, this article underscores the need for collaborative efforts and ongoing innovation to address the complex challenges of preserving digital content for future generations.